Parm to table : Italian American and American Italian recipes from Ponza to the Bronx - Petroni, Christian; Porcelli, Lesley (Harvest, an imprint of William Morrow, 2025)
"The most fun Italian-American cookbook you'll ever splatter red sauce on, with over 70 recipes from chef, restauranteur, Food Network star, and Bronx-born Italian-American Christian Petroni"-- Provided by publisher.